Redefining Management: The Impact of South Asian Generation Z’s Workplace Attitudes on Middle Managerial Roles in the Tech Industry - Fiza,Kanez; Batra,Muskan (2025)
Attitudes of Gen Z and their role in the workplace have been widely studied in the past decades. Even though Gen Z and Millennials have some similar workplace attitudes, the rapid change in technology experienced by Gen Z has inculcated some very unique working attitudes in the new generation, which in turn has impacted their expectations of middle management and their preference for such roles. Therefore, this integrative research paper explores the attitudes of South Asian Gen Z workers in the technology industry and the influence this has on middle managerial roles in the industry. The aim of this study was therefore to explore the standout traits of South Asian GenZ employees such as flexibility, value–driven motivations, concern for mental health, career aspirations and the need for work-life balance. The factors that have inculcated these traits, such as rapid advancements in technology and social media, were also studied. These traits were then utilised to study how they affect middle management expectations of this generation. Data was collected using interviews of 12 South Asian tech workers working in the EU, India and Pakistan. Seven of these were Gen Z employees, and five of these were millennial managers. The results showed the sheer need for Gen Z employees for autonomy in decision-making, the need for self-management, the need for management with exceptional interpersonal and communication skills, the desire for value-driven work, horizontal growth and the necessity for continuous learning and growth as a motivation for work. These, in turn, make the future role of middle managers as motivators and enablers rather than supervisors.